Industry Effects of Government Expenditure An Output Analysis - Bureau of Economic Analysis (Springfield U.S Department of Commerce, 1975)
This volume provides tables that contain comprehensive estimates that underlined the articles "industry effect of government expenditures: an input-output analysis" in the May 1975 survey of current business. The estimates are for 1964 and 1972 and are at the 85-industry level.
Volume 1-85, industry detail
osc 16/6/17
Loans
Keywords: Public Expenditure